Synthesis and Biological Activity of Piperine Derivatives as Potential PPARγ Agonists - Wang Y; Yao Y; Liu J; Wu L; Liu T; Cui J; Lee DYW (Dove Medical Press, 2020)
Yanli Wang,1– 3 Yuan Yao,4,5 Jing Liu,2,6 Lili Wu,7 Tonghua Liu,7 Jian Cui,1 David Yue-Wei Lee2 1School of Pharmacy, Minzu University of China, Beijing 100081, People’s Republic of China; 2Bio-Organic and Natural Products Laboratory, McLean Hospital, Harvard Medical School, Boston, MA 02478, USA; 3Key Laboratory of Plant Molecular Biology, Inner Mongolia Autonomous Region Institute of Biotechnology, Hohhot 010010, Inner Mongolia, People’s Republic of China; 4State Key Laboratory of Reproductive Regulation & Breeding of Grassland Livestock, School of Life Sciences, Inner Mongolia University, Hohhot 010070, People’s Republic of China; 5Department of Neurology, Inner Mongolia People’s Hospital, Hohhot 010017, Inner Mongolia, People’s Republic of China; 6Natural Pharmacia International Inc., Burlington, MA 01803, USA; 7School of Traditional Chinese Medicine, Beijing University of Chinese Medicine, Beijing 100029, People’s Republic of ChinaCorrespondence: David Yue-Wei LeeBio-Organic and Natural Products Laboratory, McLean Hospital, Harvard Medical School, Boston, MA 02478, USATel +1617 855 2038Email dlee@mclean.harvard.eduJian CuiSchool of Pharmacy, Minzu University of China, Beijing 100081, People’s Republic of ChinaEmail cuijian@muc.edu.cnIntroduction: Peroxisome proliferator-activated receptor γ (PPARγ) plays a key role in glucose, which is a ligand-mediated transcription factor. The lipid homeostasis often serves as a pharmacological target for new drug discovery and development.Materials and Methods: In the research, we synthesized a series of piperine derivatives and then used a fluorescence polarization-based PPARγ ligand screening assay to evaluate the agonistic activity of PPARγ. Then, we cultured human normal hepatocytes, which were treated with 100μM compounds 2a, 2t or 3d. Then, the levels of PPARγ gene were determined so as to show whether the compounds could activate or inhibit the expression of PPARγ.Results: A total of 30 piperine derivatives were synthesized and evaluated. Compound 2a was identified as a potential PPARγ agonist with IC50 at 2.43 μM, which is 2 times more potent than the positive control rosiglitazone with IC50 at 5.61μM. The human hepatocytes cells were cultured and treated with compounds 2a, 2t or 3d as described in the “Materials and Methods” section. We found that compounds 2a, 2t and 3d could activate PPARγ by 11.8, 1.9 and 7.0 times compared with the “blank”, with compound 2a activation being the most significant. Molecular docking studies indicated that the piperine derivative 2a stably interacts with the amino acid residues of the PPARγ complex active site, which is consistent with the results of the in vitro PPARγ ligand screening assay.Keywords: PPARγ, piperine derivatives, ligand screening assay, molecular docking